2021
DOI: 10.1186/s44147-021-00032-w
|View full text |Cite
|
Sign up to set email alerts
|

Urban form and economic sustainability in housing projects

Abstract: Urban areas in metropolitan cities like Cairo suffer from economic, social, and environmental predicaments. Urban economic sustainability is an approach that reforms the urban performance to gain direct benefits such as minimizing costs and maximizing profits and indirect benefits as better social, environmental, and cultural aspects. This research suggests applying such an approach to enhance Egyptian housing projects. The main research question is how to evaluate the economic sustainability of urban forms?. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…In this study, the total phenolic and flavonoid contents were similar as reported Ghaffar and El-Elaimy [35]. Moreover, Wong et al [36] screening six Hibiscus species in Malaysia and found that antioxidant properties change as a function of the environmental conditions.…”
Section: Discussionsupporting
confidence: 86%
“…In this study, the total phenolic and flavonoid contents were similar as reported Ghaffar and El-Elaimy [35]. Moreover, Wong et al [36] screening six Hibiscus species in Malaysia and found that antioxidant properties change as a function of the environmental conditions.…”
Section: Discussionsupporting
confidence: 86%
“…For (Karjalainen & Juhola, 2021), in particular, this ICT growth should be aimed towards low carbon enterprises, where extensive use of intelligent technologies may enhance the economy and speed up the move toward environmental sustainability. Complementary usage of ICT with the transportation system allows people to make choices that affect the total demand for transport and on alternative models, such as increasing the viability of working from home or promoting a switch in mobility modes (Ghaffar & El Aziz, 2021;Ren et al, 2020;Tang et al, 2020).…”
Section: Overview Of Intelligent Transport Systemsmentioning
confidence: 99%
“…Common indicators include land utilization, material selection, and energy conservation, water efficiency, and waste and emissions minimization. In general terms, economic sustainability refers to practices that support economic growth in the long term without negative impacts on a community's social, environmental, and cultural spheres [14]. In the built environment economic sustainability focuses on reducing capital, operating, and disposal costs during the lifecycle of a facility.…”
Section: Sustainability -The Triple Bottom Linementioning
confidence: 99%